NEOTECTONICS OF THE NORTHERN NORWEGIAN-GREENLAND BASIN: SPECIFIC FEATURES AND EVOLUTION OF THE KNIPOVICH RIDGE AND POMORSKY PERIOCEANIC TROUGH - Shipilov E.V.; Shkarubo S.I.; Raznitsin Yu.N. (My University, 2006)
The Earth’s crust beneath the Atlantic Ocean has a heterogeneous tectonic structure. The northern (Arctic and subarctic) region is characterized by a particularly specific structure. The region is located between two demarcation fracture zones. The Spitsbergen fracture zone, which separates the study region from structures of the Polar Basin, is situated in the north. The Charley Gibbs fracture zone (52° N) is located in the south. The Reykjanes spreading ridge, which extends from Iceland to the southwest, is obviously a member of the Mid-Atlantic Ridge system.